Policy effects of the elasticity of substitution across labor types in life cycle models - Cassou, Steven P.; Gorostiaga, Arantza; Uribe Zubiaga, Iker (My University, 2013)
This paper investigates how the production function elasticity of substitution across different labor types impacts the results of policy analysis in multiperiod lived agent overlapping generations models. We critique and investigate the popular structure that simply assumes that workers with different age, experience or education are perfectly substitutable in production. This structure is inconsistent with empirical evidence of production complementarities. We couch our findings in the context of two types of policy reforms: a social security reform and a tax reform. These reforms were chosen in part not only because of the large interest in them, but also because of their differing effects on life cycle decisions. We find that ignoring production complementarity may influence the conclusions of policy analysis.
Keywords: Labor complementarity; Overlapping generations model; Fiscal policy reform; Social security reform